Pathological presentation of cardiac mitochondria in a rat model for chronic kidney disease. - Einat Bigelman; Lena Cohen; Genya Aharon-Hananel; Ran Levy; Zach Rozenbaum; Ann Saada; Gad Keren; Michal Entin-Meer (PLoS ONE, 2018)
Background Mitochondria hold crucial importance in organs with high energy demand especially the heart. We investigated whether chronic kidney disease (CKD), which eventually culminates in cardiorenal syndrome, could affect cardiac mitochondria and assessed the potential involvement of angiotensin II (AngII) in the process. Methods Male Lewis rats underwent 5/6 nephrectomy allowing CKD development for eight months or for eleven weeks. Short-term CKD rats were administered with AngII receptor blocker (ARB). Cardiac function was assessed by echocardiography and cardiac sections were evaluated for interstitial fibrosis and cardiomyocytes' hypertrophy. Electron microscopy was used to explore the spatial organization of the cardiomyocytes. Expression levels of mitochondrial content and activity markers were tested in order to delineate the underlying mechanisms for mitochondrial pathology in the CKD setting with or without ARB administration. Results CKD per-se resulted in induced cardiac interstitial fibrosis and cardiomyocytes' hypertrophy combined with a marked disruption of the mitochondrial structure. Moreover, CKD led to enhanced cytochrome C leakage to the cytosol and to enhanced PARP-1 cleavage which are associated with cellular apoptosis. ARB treatment did not improve kidney function but markedly reduced left ventricular mass, cardiomyocytes' hypertrophy and interstitial fibrosis. Interestingly, ARB administration improved the spatial organization of cardiac mitochondria and reduced their increased volume compared to untreated CKD animals. Nevertheless, ARB did not improve mitochondrial content, mitochondrial biogenesis or the respiratory enzyme activity. ARB mildly upregulated protein levels of mitochondrial fusion-related proteins. Conclusions CKD results in cardiac pathological changes combined with mitochondrial damage and elevated apoptotic markers. We anticipate that the increased mitochondrial volume mainly represents mitochondrial swelling that occurs during the pathological process of cardiac hypertrophy. Chronic administration of ARB may improve the pathological appearance of the heart. Further recognition of the molecular pathways leading to mitochondrial insult and appropriate intervention is of crucial importance.